Effects of a five-day smoking cessation program on the smoking behaviors of selected high school students in Manila and Cavite - Deressa, Geneti (1987)
This study determined smoking prevalence and examined some psychosocial factors associated with smoking among selected high school students in Manila, Makati and Cavite. It also evaluated the effect of a 5-day smoking cessation program on the smoking behavior of the students. 5 schools, 3 from urban and 2 from rural areas, comprising 834 students were involved in determining the prevalence of smoking. To evaluate the effect of the program, only 4 schools--2 from each area--were used. 1 school constituted the experimental group and the other school the control group. The experimental group was exposed to the 5-day smoking cessation program and followed-up in 7 weeks to assess changes in their smoking behavior. 3 observations were made in the experimental group and 2 in the control group. Measures of success of the program were based on: Quit rate, Reduction Rate, Relapse Rate, Changes in Attitude and Changes in Knowledge. The chi-square test was used to examine the association between smoking and psychosocial factors, while the t-test was used to find out whether there were significant differences between the experimental and control groups in knowledge, attitude and amount of cigarette consumed per day at pretest and posttest follow-ups. The overall prevalence of smoking was 20.9 . Significantly a higher proportion of smokers was found in: exclusive private schools (37.6 ) than in public schools (16.0 ); in urban schools (26.4 ) as against rural schools (12.9 ); among boys (27.9 ) than among girls (15.4 ); and among 4th year (22.1 ) than among either 3rd (13.4 ), 2nd (14.0 ) or 1st year (18.9 ). The mean age of 1st experience with smoking was found higher for boys (X = 13.3) than for girls (X = 11.9) which was an indication that girls started smoking earlier than boys. The critical age for both sexes was 13. However, there was no significant difference between boys and girls in the amount smoked per day. The factors that were significantly associated with the smoking behavior of the students were: high socio-economic status (as measured on education and occupation), parental smoking habit (specially mothers), elder brothers and sisters, boy/girl friends, best friends and teachers' smoking habits. Of situational factors--going to disco, watching movies and dating were significantly associated with smoking. However, singing and reading were significantly association with non-smoking behavior of the subjects. Among factors related to schools--low academic achievement (low G.P.A.) and reapeating classes--were significantly associated with smoking, while competition and absenteeism were not. On personality variables there was no significant difference between smokers and non-smokers. Personal autonomy over decision remained the same for both smokers and non-smokers. Nonetheless, future intention to smoke was found congruous with current smoking habits. This intention was found to be stronger for boys than for girls. Similarly, attitudes toward smoking were found consonant with smoking behavior, but there was no significant difference between smokers and non-smokers on heir level of awareness about health risks associated with smoking at pretest.